JAMUR ENDOSIOMBION SI BINTANG LAUT (Asterias forbesi ) SEBAGAI ALTERNATIF ANTIBAKTERI BARU PADA BAKTERI PENYEBAB INFEKSI SALURAN PENCERNAAN - Rusli, Rusli; Fajri, Muh Danial; Sari, A. Sri Nila; Asmasari, Nur (Jurnal Ilmiah As-Syifaa, 2016)
Search of new antibacterial compounds, continuously carried out in line with the increasing number of new diseases emerging, ranging from infectious diseases, cancer and other dangerous diseases. Bioactive compounds can be obtained from several sources, including from plants, animals, microbes and marine organisms, one of which is a starfish, including the endosymbiont. The research of activity fungal isolates endosymbiont on the starfish Asterias forbesi types have been carried out in order to get a fungal isolates that have activity eradicate pathogenic bacteria, especially in the gastrointestinal tract. This research method is isolation of fungal endosymbionts on the sample starfish with Potato Dextrose Agar Chloramfenikol (PDAC) medium at room temperature for 3x24 hours. Endosymbiont fungal isolates was purified by the quadrant method, until pure fungal isolates obtained, then do the fermentation with Yeast Maltose Broth (MYB) medium on shaker at a speed of 200 rpm for 14x24 hours. The Results of fermentat continued antibacterial activity using agar diffusion method. The Results isolation of fungal endosymbiont on Starfish Asterias forbesi types obtained five (5) pure fungal isolates endosymbiont. From the results of fermentation obtained test results that indicate the antibacterial activity of fungal isolates endosymbiont on Starfish (Asterias forbesi) provide activity against Pseudomonas aeruginosa, Â Eschericia coli, Salmonella thypi,Â  Shigella dysentriae, Staphylococcus auerus, and Vibrio cholerea bacterial. The conclusions in this study was isolate fungal endosymbionts IJBL FF-UMI 04 the most active inhibits all the bacterial test. Isolates with the greatest inhibit zone is isolate IJBL FF-UMI 03 on the test bacteria Salmonella thypi of 21.3 mm.